2019
DOI: 10.5194/bg-16-505-2019
|View full text |Cite
|
Sign up to set email alerts
|

Export fluxes of dissolved inorganic carbon to the northern Indian Ocean from the Indian monsoonal rivers

Abstract: Abstract. Rivers are an important source of dissolved inorganic carbon (DIC) to the adjacent coastal waters. In order to examine the spatial variability in the distribution and major sources of DIC in the Indian monsoonal rivers and to quantify their export flux to the northern Indian Ocean, 27 major and medium-sized rivers were sampled during the discharge period. Significant spatial variability in concentrations of DIC (3.4–73.6 mg L−1) was observed, and it is attributed to spatial variations in the precipit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 83 publications
(118 reference statements)
1
3
0
Order By: Relevance
“…Such a significantly higher DIC export rate, as compared to POC export rate, has been also observed in various other mangrove dominated estuarine systems. Yearly riverine DIC export rates normalized by catchment area were in the same order of magnitude as those reported for several (sub-)tropical estuarine systems of similar size along the coast of Sumatra, Indonesia (Wit et al, 2018), the coast of India (Krishna et al, 2019) as well as one system in Cameroon (Brunet et al, 2009). These DIC export rates were even comparable to rates from larger (sub-)tropical estuaries (Cai et al, 2008) including the Pearl river estuary, China (Guo et al, 2008) and Yangtze river estuary, China (Wu et al, 2007).…”
Section: Carbon Export To the Gulf Of Guayaquilsupporting
confidence: 73%
“…Such a significantly higher DIC export rate, as compared to POC export rate, has been also observed in various other mangrove dominated estuarine systems. Yearly riverine DIC export rates normalized by catchment area were in the same order of magnitude as those reported for several (sub-)tropical estuarine systems of similar size along the coast of Sumatra, Indonesia (Wit et al, 2018), the coast of India (Krishna et al, 2019) as well as one system in Cameroon (Brunet et al, 2009). These DIC export rates were even comparable to rates from larger (sub-)tropical estuaries (Cai et al, 2008) including the Pearl river estuary, China (Guo et al, 2008) and Yangtze river estuary, China (Wu et al, 2007).…”
Section: Carbon Export To the Gulf Of Guayaquilsupporting
confidence: 73%
“…PBC is the concentration at the lowest sampling site (i.e., outlet), and Q is the annual discharge taken from the existing literature [29,30].…”
Section: Estimation Of Export Fluxes and Yieldsmentioning
confidence: 99%
“…Comprehensive export flux estimates of PBC based solely on the suspended matter samples are sparse (figure 1(a)). Flux of PBC in this study was estimated for the Sabarmati, Mahi, and Ambika rivers using the PBC concentrations at downstream sites with discharge data from Krishna et al [29]. This led to export fluxes of 0.589, 4.400, and 0.723 Gg yr −1 of PBC from the Sabarmati, Mahi, and Ambika rivers, respectively.…”
Section: Transformation Of Particulate Black Carbon In Engineered Sys...mentioning
confidence: 99%
“…Only a few DIC yield data similar to this study have been reported, for example in the Brahmaputra River, India-Bangladesh (14.4 t C km 2 yr −1 ); Xijiang, China (15.38 t C km 2 yr −1 ); and Pearl, China (13.2 t C km 2 yr −1 ) [99], as well as in other small monsoon rivers in India, such as the Netravati (17.8 t C km 2 yr −1 ) and Baitarani (20.7 t C km 2 yr −1 [138]. Higher DIC yields have been reported in the tropical mountainous watersheds of western India, such as the Ulhas River (48.5 t C km 2 yr −1 [139] or the Kikori River, New Guinea (74.6 t C km 2 yr −1 ), which has the highest value globally [34].…”
Section: Global C Export From the Usumacinta-grijalva River To The Gu...mentioning
confidence: 99%